Writing Tamil Catholicism Literature, Persuasion and Devotion in the Eighteenth Century - Trento, Margherita (Brill, 2022)
In Writing Tamil Catholicism: Literature, Persuasion and Devotion in the Eighteenth Century, Margherita Trento explores the process by which the Jesuit missionary Costanzo Giuseppe Beschi (1680-1747), in collaboration with a group of local lay elites identified by their profession as catechists, chose Tamil poetry as the social and political language of Catholicism in eighteenth-century South India. Trento analyzes a corpus of Tamil grammars and poems, chiefly Beschi's Tēmpāvaṇi, alongside archival documents to show how, by presenting themselves as poets and intellectuals, Catholic elites gained a persuasive voice as well as entrance into the learned society of the Tamil country and its networks of patronage. This project has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 840879.